Daily supplementation with the Lab4P probiotic consortium induces significant weight loss in overweight adults - D. R. Michael (Nature Portfolio, 2021)
Abstract This 9-month randomised, parallel, double-blind, single-centre, placebo-controlled study (PROBE, ISRCTN18030882) assessed the impact of probiotic supplementation on bodyweight. Seventy overweight Bulgarian participants aged 45–65 years with BMI 25–29.9 kg/m2 received a daily dose of the Lab4P probiotic comprising lactobacilli and bifidobacteria (50 billion cfu/day). Participants maintained their normal diet and lifestyle over the duration of the study. The primary outcome was change from baseline in body weight and secondary outcomes included changes in waist circumference, hip circumference and blood pressure. A significant between group decrease in body weight (3.16 kg, 95% CI 3.94, 2.38, p < 0.0001) was detected favouring the probiotic group. Supplementation also resulted in significant between group decreases in waist circumference (2.58 cm, 95% CI 3.23, 1.94, p < 0.0001) and hip circumference (2.66 cm, 95% CI 3.28, 2.05, p < 0.0001) but no changes in blood pressure were observed. These findings support the outcomes of a previous shorter-term Lab4P intervention study in overweight and obese participants (PROMAGEN, ISRCTN12562026). We conclude that Lab4P has consistent weight modulation capability in free-living overweight adults.